2011
DOI: 10.1371/journal.pone.0027760
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Mechanisms of Multiple Insecticide Resistance in a Population of the Malaria Vector Anopheles funestus in Benin

Abstract: BackgroundThe insecticide resistance status of the malaria vector Anopheles funestus and the underlying resistance mechanisms remain uncharacterised in many parts of Africa, notably in Benin, West Africa. To fill this gap in our knowledge, we assessed the susceptibility status of a population of this species in Pahou, Southern Benin and investigated the potential resistance mechanisms.Methodology/Principal FindingsWHO bioassays revealed a multiple resistance profile for An. funestus in Pahou. This population i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
125
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(145 citation statements)
references
References 37 publications
19
125
0
Order By: Relevance
“…The pyrosequencing AB software was used to design three sequence-specific primers for Ace-1 and kdr mutations (the L1014F and L1014S kdr-variants are detected in the same assay). The sequences for genotyping analysis and the dispensation order for both reactions are the same as previously described (40). Target DNA fragments for kdr and Ace-1 were first amplified by PCR using the forward and biotinylated reverse primers.…”
Section: Methodsmentioning
confidence: 99%
“…The pyrosequencing AB software was used to design three sequence-specific primers for Ace-1 and kdr mutations (the L1014F and L1014S kdr-variants are detected in the same assay). The sequences for genotyping analysis and the dispensation order for both reactions are the same as previously described (40). Target DNA fragments for kdr and Ace-1 were first amplified by PCR using the forward and biotinylated reverse primers.…”
Section: Methodsmentioning
confidence: 99%
“…funestus [63,64,71,72]. However, a multiple insecticide resistance profile has been recently observed in Benin [74]. Insecticide resistance is an threat to effective malaria control.…”
Section: Insecticide Susceptibility and Vector Controlmentioning
confidence: 99%
“…Both colonies have been recurrently used in insecticide resistance studies of An. funestus [74,79,80]. Indeed, it is one of these colonies (FUMOZ), which has been elected as reference An.…”
Section: Introductionmentioning
confidence: 99%
“…16 Furthermore, GSTE2 gene displays the highest level of conservation among all the GSTEs in Anopheles species whereas the GSTE5 gene is evolving under positive selection. 62 The negative selection curbing AgGSTE2 sequence divergence favors its DDT dehydrochlorinase activity, the highest ever reported for any GST enzyme 13,14 On the other hand, several sites in AgGSTE5 are under positive selection: 4 residues in the N-terminal domain, where the binding of glutathione occurs (G-site), and 14 residues in the substrate-binding site (H-site). 63 The increased rate of non-similar amino acid replacements in the G-site and H-site strongly suggest that AgGSTE5 is undergoing selective pressure to express dehydrochlorinase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported resistance to dichlorodiphenyl-trichloroethane (DDT) and other insecticides by this species. [11][12][13] It has been shown that the GST Epsilon class isoform 2 from A. gambiae (AgGSTE2) is associated to DDT resistance via two mechanisms: elevated gene expression and catalytic activity of the recombinant enzyme. 14 For this reason, AgGSTE2 is overexpressed in resistant strains and the recombinant protein is efficient at metabolizing DDT.…”
Section: Introductionmentioning
confidence: 99%